Menyingkap perkembangan perbandaran Ipoh menjadi sebuah bandaraya - Ibrahim Mohd Hairy, Md. Jahi Jamuluddin, Hadi Abdul Samad, Ariffin Khairi, (N/A, 2011)
Menyingkap perkembangan perbandaran Ipoh menjadi sebuah bandaraya by Ibrahim Mohd Hairy, Md. Jahi Jamuluddin, Hadi Abdul Samad, Ariffin Khairi,